2010
DOI: 10.1038/ki.2010.106
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acids within urinary exosomes/microvesicles are potential biomarkers for renal disease

Abstract: Urinary exosomes or microvesicles are being studied intensively to identify potential new biomarkers for renal disease. We sought to identify whether these microvesicles contain nucleic acids. We isolated microvesicles from human urine in the same density range as that previously described for urinary exosomes and found them to have an RNA integrity profile similar to that of kidney tissue, including 18S and 28S rRNA. This profile was better preserved in urinary microvesicles compared with whole cells isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
331
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 384 publications
(342 citation statements)
references
References 24 publications
9
331
0
2
Order By: Relevance
“…Previous studies suggested that urinary miRNAs, like circulating miRNAs in other body fluids, are derived from tissues and cells in the presence of ongoing disease (32,33). In general, cellular miRNAs can passively leak from damaged cells or can be actively secreted into the extracellular space or circulation via the microvesicle pathway (34,35) or within HDL protein complexes (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that urinary miRNAs, like circulating miRNAs in other body fluids, are derived from tissues and cells in the presence of ongoing disease (32,33). In general, cellular miRNAs can passively leak from damaged cells or can be actively secreted into the extracellular space or circulation via the microvesicle pathway (34,35) or within HDL protein complexes (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…10,22,23 After these vesicles fuse with the plasma membranes of the parent cell, they are released as exosomes into the extracellular environment ( Figure 1). Interestingly, the lipid-bilayered exosomes seem to be protected from RNAses, 24,25 sheltering the genetic cargo in exosomes. In addition, vesicles can transport biologic cargo to not only neighboring cells but also, relatively long distanced.…”
Section: Characterization Of Evsmentioning
confidence: 99%
“…At the moment, proteomic analyses are not yet feasible for broad clinical application. Analyses of RNAs, in particular microRNAs, might be another potential diagnostic approach (336,415). This approach, either on biopsy tissue or in urine, is emerging as a promising approach for improving the diagnostic and predictive value of rejection, fibrosis development and graft loss in kidney transplantation (416)(417)(418)(419).…”
Section: Serum and Urine Biomarkersmentioning
confidence: 99%